Annual review of high performance coaching and consulting 2011 (International Journal of Sports Science and Coaching, 2012)
In 2009 Carol Kauffman founded the Institute of Coaching at Harvard, having been the Founding Director of the Coaching and Positive Psychology Initiative (2007-2008), at the McLean Hospital in the Harvard Medical School. Kauffman has recently stated that in coaching we are "at a stage in our development where we can describe what we do as `technical eclecticism`"; i.e., "we can pull interventions from a bunch of different buckets and see what works and have some understanding of the worldviews and theoretical schools of thought that inform those techniques". Kauffman presents her PERFECT model which is similar to Arnold Lazarus` Multimodal Therapy (MMT) model in psychotherapy.